Presumed Innocent - Turow, Scott (New York Warner Books, 1987)
Rusty Sabich is an up-and-comer in the county prosecutor's office. He's intelligent, hard working, dependable. And, just maybe, he's also a murderer.
Keywords: Kindle County (Imaginary place) -- Presumption of innocence -- American fiction